On the Etymology of the Yoruba Theonym Shango - Sandro Capo Chichi (Yoruba Studies Review)
This paper revisits the contested origins of Shango, a prominent Yoruba deity associated with thunder, lightning, and kingship. While Yoruba tradition often portrays Shango as an early king of Oyo who was deified, such accounts present inconsistencies. By examining linguistic evidence, the author proposes that the name Shango derives from the Gbari term ɛtswaʃɛ̰gʷo (ruler of the sky) and entered Old Oyo Yoruba via Nupe. In Gbari cosmology, ɛtswaʃɛ̰gʷo denotes a sky god, while in Nupe the borrowed form etsu ʃjə̰gʷo was reinterpreted as “King ʃjə̰go,” thereby blending notions of rulership with divine power. This linguistic shift, the paper argues, set the stage for Yoruba tradition to merge the idea of a thunder deity with an actual royal figure, giving rise to Shango’s dual identity as both a celestial power and an Oyo king.